Struktur Kelompok, Daerah Jelajah, dan Jenis Makanan Ungko (Hylobates agilis) di Hutan Pendidikan dan Penelitian Biologi Universitas Andalas - Yunila Berliana; - Rizaldi; Wilson Novarino (Universitas Andalas, 2013)
A study on group structures, home ranges and plant species eaten by agile gibbons (Hylobates agilis) at The Biological Education and Research Forest, Andalas University was conducted from June to November 2012. Group structures were figured out through direct count method during field surveys, while plants eaten by the gibbons were recorded using ad-libitum observation. There were 15 gibbons which belong to three monogamous groups. Structure of the groups consisted of one adult male and one adult female, one subadult, 1-2 juveniles, and 0-1 infant. Sex ratio of the population was 1.1 : 1. Average home range was 10.9 ha. Population density of the gibbons in a defined area of 62.76 ha was 23.9 individu/km2 and group density was 4.78 group/km2. There were 17 species of plant eaten by the gibbons, those species belong to 11 families, where the highest number of species belong to Euphorbiaceae and Moraceae.Keywords: Hylobates agilis, group structure, home range, food plant